Assessing and modeling the dynamics and persistence of mussels in rocky-shore microhabitats - Barbosa, Romina Vanessa; Bacher, Cédric; Jean, Fred; Jaud, Marion; Ammann, Jérôme; Thomas, Yoann (Marine environmental research, 2025)
In intertidal rocky shores, sessile organisms are subject to local variations due to a complex interplay of physical and biological drivers. Here, we examined the patterns and the dynamics of the distribution of a key benthic ecosystem-engineer species, the mussel Mytilus galloprovincialis. We characterized areas of loss, gain, and persistence of mussel space occupancy using drone images with a resolution of 1 cm across two rocky shores spanning 3121 m2 and 3499 m2. Then, we assessed the effect of microhabitat slope, microhabitat orientation, and intertidal height on the characteristics of mussel distribution for the two rocky shores. Notably, substantial losses ranged from 56 % to 80 % depending on the rocky shore. The hierarchical impact of habitat topographic features on mussel occupancy diminishes in the order of rocky shore, intertidal height, and microhabitat features. To unravel the dynamics further, we calculated persistence, resilience, and the time to recover from disturbance using a Markov Chain model. Persistence time decreased at the extremes of the rocky shore —both its top and bottom edges. Contrary to expectations, mussels at these extremities exhibit higher resilience, preventing their disappearance despite significant losses. Our results provide insights into the structural dynamics and emphasize the need to consider long-term responses to environmental changes. This study underscores the potential of integrating models with drone technology for monitoring intertidal populations, offering a powerful tool to comprehend and anticipate the enduring impacts of environmental shifts on spatial distribution. •Changes of mussel covered area were evaluated from drone images in two rocky shores.•More than 50 % mussel area were lost between June 2019 and June 2020.•Mussel distribution dynamics varied between rocky shores and along the intertidal height.•Markov chain model showed higher resilience at upper and bottom intertidal edges.•Combining model and drone allows assessing long-term dynamics of intertidal species.